2018
DOI: 10.3390/nu10050535
|View full text |Cite
|
Sign up to set email alerts
|

Household Food Insecurity as a Predictor of Stunted Children and Overweight/Obese Mothers (SCOWT) in Urban Indonesia

Abstract: (1) Background: The double burden of malnutrition has been increasing in countries experiencing the nutrition transition. This study aimed to determine the relationship between household food insecurity and the double burden of malnutrition, defined as within-household stunted child and an overweight/obese mother (SCOWT). (2) Methods: A cross-sectional survey was conducted in the urban city of Surabaya, Indonesia in April and May 2015. (3) Results: The prevalence of child stunting in urban Surabaya was 36.4%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 30 publications
(48 reference statements)
5
38
0
7
Order By: Relevance
“…Studies conducted in Iran and Bangladesh [ 23 , 28 ] indicated that limited access to community health services in remote areas with difficult or no access to clean water for drinking and bathing are most common in rural areas and these are enhancing risk factors for stunting [ 2 , 25 ]. On the contrary, the higher SES group more likely to have better food security in their families [ 10 ]. As a consequence, children could provide meals better in quantitively and qualitatively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Iran and Bangladesh [ 23 , 28 ] indicated that limited access to community health services in remote areas with difficult or no access to clean water for drinking and bathing are most common in rural areas and these are enhancing risk factors for stunting [ 2 , 25 ]. On the contrary, the higher SES group more likely to have better food security in their families [ 10 ]. As a consequence, children could provide meals better in quantitively and qualitatively [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the higher SES group more likely to have better food security in their families [ 10 ]. As a consequence, children could provide meals better in quantitively and qualitatively [ 10 ]. Moreover, a low-quality living environment, as often found in poor education families with low income, in addition to low-quality food and repeated episodes of illnesses may reduce immunity, which in turn may result in higher vulnerability—especially for diarrhea, respiratory diseases and infection diseases [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sample, 163 (11.3%) of children who were stunted had overweight or obese mothers. This phenomenon, whereby stunted children and overweight or obese mothers reside within the same household highlights the double burden of malnutrition that are particularly prevalent in countries undergoing a nutrition transition (34).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 163 (11.3%) of children who were stunted had overweight or obese mothers. This phenomenon, whereby stunted children and overweight or obese mothers reside within the same household highlights the double burden of malnutrition that are particularly prevalent in countries undergoing a nutrition transition (35).…”
Section: Sample Characteristicsmentioning
confidence: 99%